2017
DOI: 10.5021/ad.2017.29.6.706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cooking Methods on Histamine Levels in Selected Foods

Abstract: BackgroundHistamine in food is known to cause food poisoning and allergic reactions. We usually ingest histamine in cooked food, but there are few studies about the influence of cooking method on the histamine level.ObjectiveThe purpose of this study was to determine the influence of cooking methods on the concentration of histamine in foods.MethodsThe foods chosen were those kinds consumed frequently and cooked by grilling, boiling, and frying. The histamine level of the food was measured using enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Research data about the effects of different cooking methods on histamine concertation showed the increase of histamine concentrations after grilling or frying, but boiling had little effect on histamine levels in fish meat. The authors believe that the reason for these changes may be the moisture evaporation during grilling or frying, which elevates the histamine concentration (Chung et al, 2017). Adams et al (2018) proved that the process of precooking during the production of canned tuna or frozen tuna suppresses the formation of histamine for 12 h or longer after precooking.…”
Section: Histamine Levels In Canned Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Research data about the effects of different cooking methods on histamine concertation showed the increase of histamine concentrations after grilling or frying, but boiling had little effect on histamine levels in fish meat. The authors believe that the reason for these changes may be the moisture evaporation during grilling or frying, which elevates the histamine concentration (Chung et al, 2017). Adams et al (2018) proved that the process of precooking during the production of canned tuna or frozen tuna suppresses the formation of histamine for 12 h or longer after precooking.…”
Section: Histamine Levels In Canned Fishmentioning
confidence: 99%
“…Although histidine decarboxylase activity decreased at high temperature, histamine production would continue until the enzyme became inactive i.e. the histamine in fish meat would accumulate during heat treatment until the enzyme was inactive (Kanki et al,2007, Chung et al, 2017.…”
Section: Histamine Levels In Canned Fishmentioning
confidence: 99%
“…It was also observed that the histamine level increased in foods after frying and grilling [41]. However, other authors elucidated the mechanism by which certain cooking ingredients and common organic acids destroy histamine [42], so it could be very interesting to deepen this aspect by considering the occurrence of bio-compounds that develop following the roasting process of cocoa and their possible role in the control of the BAs levels in food.…”
Section: Effect Of Roasting On the Bas Contentmentioning
confidence: 99%
“…Moreover, histamine is reported to be present, in different quantities, in foods and beverages . Fish and fish products, dairy products, meat and meat products, fermented vegetable and soy products are reported to contain high levels of histamine and in beverages it is present, for example, in wine and beer ,. It is well known that high levels of histamine in the body introduced by food and beverage ingestion can cause health problems similar to a common food allergy such as, headache, migraines, hypertensive crisis, swelling, rashes, hives, asthma, and many gastrointestinal diseases such as nausea, diarrhea etc ,.…”
Section: Introductionmentioning
confidence: 99%